Socialism with Haitian Characteristics - Paul C. Mocombe (Studies in Social Science & Humanities, 2024)
This work argues that following the Haitian Revolution, which is a revolt against slavery and mercantilist capitalism, the founder of the country, Jean-Jacques Dessalines, attempted to synthesize three forms of system and social integration on the island in order to constitute the nation of Haiti: the mercantilist and liberal capitalism of the Affranchis, petit-bourgeois blacks and mulatto elites, respectively; and the Lakouism, communism, of the African majority on the island. In this sense, Dessalines, represented the first embodiment of Kojève’s end of history Hegelian thesis, and defined Haiti’s socialism, what Mocombe calls libertarian communism, with its Haitian characteristics.